Nanoscale Vectorial Electric and Magnetic Field Measurement - Eismann, Jörg S.; Banzer, Peter (ACS Photonics, 2024)
In technology, old or new, from basic imaging through a camera lens to advanced applications such as fluorescence microscopy and optical lithography, there are countless examples that would be inconceivable without the utilization of focused light. As technology evolves, the demands on spatially confined light fields grow but so do the challenges of accurately characterizing these complex fields. This study introduces a technique to measure the full vectorial nature of light, reaching sub/wavelength spatial resolution while capturing the 3D amplitude and phase for both electric and magnetic fields. This is achieved based on a polarization-resolved far-field analysis of light scattered by a single spherical nanoparticle acting as a local probe. For experimental verification, the method is applied to tightly focused light fields under various input scenarios. Offering high resolution, precision, and flexibility, this technique shows great promise for both fundamental research and applications in technologies relying on highly localized light fields.
CRIS-Team Scopus Importer:2025-02-04
Keywords: electromagnetic field metrology; nanoscale; scattering; tight focusing; vectorial fields